Analisis Integritas Data Dalam Mekanisme Berbagi File Google Drive: Studi Kasus Pengujian End-To-End: Data Integrity - Aan; Kholik Prasojo; Nurul Aulia Rais (PT. Global Research Collaboration, 2025)
Ensuring data integrity is a critical aspect of cloud storage systems, especially in file-sharing mechanisms between users. This study aims to analyze how well Google Drive preserves data integrity during file transfers by employing an end-to-end testing approach. The method used is experimental, involving a systematic procedure: creating test files in various formats, calculating initial hash values, uploading them to Google Drive, downloading from different accounts or devices, and re-calculating the hash values after transfer. The results show that hash values remain identical before and after the file-sharing process across all tested files, ranging from small text documents to large ISO files. These findings indicate that Google Drive reliably maintains data integrity during cross-user and cross-device sharing, with no undetected modifications to file contents. This study contributes to a technical understanding of data reliability within modern cloud storage services.